Evaluating of the UV resistance of cross laminated timber - Yan, Yoki (Nanyang Technological University, 2021)
This report explores the use of titanium dioxide (TiO2) particles, bis(1-octyloxy-2,2,6,6-tetramethyl-4-piperidyl) sebacate, 2-hydroxy-4-methoxybenzophenone, and 1,3-diphenyl-1,3-propanedione in protecting cross laminated timber (CLT) assembled from spruce timber from UV degradation. Different mixtures of the additives were also investigated. These additives were thoroughly dispersed into D.E.R. 331 epoxy resin and cured with Ancamine 2686 curing agent. The prepared coatings were then coated thinly on the surface of CLT. UV-Vis absorbance and transmittance as well as ATR-FTIR absorbance analysis were done on the coatings. A 28-day accelerated weathering test was conducted on the coated CLT. Changes in chemical structure after weathering were observed with the ATR-FTIR. Changes in contact angles of the coated CLT after weathering were investigated. Lastly, colour stability of the coated CLT after weathering were quantified. The results obtained showed that the coatings applied on the CLT were generally effective in improving the colour stability and reducing changes in chemical structure of CLT. Contact angles of the coated wood were also observed to have increased after weathering.